REDESAIN STRUKTUR GEDUNG TRAINING CENTER UNIMA MENURUT PERATURAN SNI 2019 (Sustainable Construction (SUSCON), 2024)
The regulations relating to planning earthquake resistant building structures in Indonesia are SNI 1726:2019 Procedures for Earthquake Resistance Planning for Building and Non Building Structures This Training Center building was planned in 2015 at that time it was still using the old regulations namely SNI 2847:2013 and SNI 1726:2012 so a re planning or redesign will be made using the latest regulations in force in Indonesia namely SNI 2847:2019 for concrete and SNI 1726:2019 for earthquakes This research was conducted at the location of the Unima Training Center Building Based on the results of the redesign of the Unima Training Center Building with the 2019 SNI regulations it was obtained that the reinforcement results in the beams and columns still met the standards according to SNI < p>
Keywords: Redesign; Building Structure; UNIMA; 2019 SNI Regulations